Nucleic acid amphiphiles: Synthesis, properties, and applications - Amu Gubu; Xueli Zhang; Aiping Lu; Baoting Zhang; Yuan Ma; Ge Zhang (Elsevier, 2023)
Nucleic acid amphiphiles, referring to nucleic acids modified with large hydrophobic groups, have been widely used in programmable bioengineering. Since nucleic acids are intrinsically hydrophilic, the hydrophobic groups endow nucleic acid amphiphiles with unique properties, such as self-assembling, interactions with artificial or biological membranes, and transmembrane transport. Importantly, the hybridization or target binding capability of oligonucleotide itself supplies nucleic acid amphiphiles with excellent programmability. As a result, this type of molecule has attracted considerable attention in academic studies and has enormous potential for further applications. For a comprehensive understanding of nucleic acid amphiphiles, we review the reported research on nucleic acid amphiphiles from their molecular design to final applications, in which we summarize the synthetic strategies for nucleic acid amphiphiles and draw much attention to their unique properties in different contexts. Finally, a summary of the applications of nucleic acid amphiphiles in drug development, bioengineering, and bioanalysis are critically discussed.